2021
DOI: 10.17509/ijcsne.v1i2.33405
|View full text |Cite
|
Sign up to set email alerts
|

Municipal COVID-19 Epidemiological Response: Level of Satisfaction among Households in Esperanza, Sultan Kudarat

Abstract: This study was carried out to statistically quantify the level of satisfaction among residents in Esperanza, Sultan Kudarat, and the level of effectivity of the municipal COVID- 19 epidemiological response team on COVID- 19 response. In the Philippines, from the initial studies and information about the nature and behavior of the virus, the government settles on a plan of action around what mitigation strategies and control measures to implement. This present study was conducted to find out the level of satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Overall, the results established that barangays are responsive enough with their responsibility of implementing IATF protocols. This is in parallel to the findings of a previous study where they found that there's a level of effectiveness on the implementation of public health and safety protocols on the households of a particular community in Mindanao (Lasanas et al, 2021). 4 indicates the significant difference on the assessment of barangay officials and residents on the implementation of IATF protocols.…”
Section: Resultssupporting
confidence: 83%
“…Overall, the results established that barangays are responsive enough with their responsibility of implementing IATF protocols. This is in parallel to the findings of a previous study where they found that there's a level of effectiveness on the implementation of public health and safety protocols on the households of a particular community in Mindanao (Lasanas et al, 2021). 4 indicates the significant difference on the assessment of barangay officials and residents on the implementation of IATF protocols.…”
Section: Resultssupporting
confidence: 83%
“…The Covid-19 pandemic that has occurred in several countries will continue until 2021 for an indefinite time limit. Vaccine injections have been carried out by almost all countries, including Indonesia, but people still have to comply with health protocols (Lasanas et al, 2021). Regular physical activity is a major health behavior from a public health perspective, because it has a tremendous impact on health.…”
Section: Introductionmentioning
confidence: 99%